Research on nursing unit layouts: an integrative review. Issue 9 (6th July 2015) - Rashid, Mahbub
Abstract : Purpose: – This paper aims to present an integrative review of the research studies on nursing unit layouts. Design/methodology/approach: – Studies selected for review were published between 1956 and 2014. For the purpose of this review, a framework for integrative review was developed using research orientations. The three primary dimensions – technical, psychological and social – of the designed environment and various combinations of these dimensions were used to define the research orientations of these studies. Findings: – Of all the publications reviewed for the paper, 21 presented technical orientations, 16 psychological orientations, 3 social orientations, 20 psychotechnical orientations, 10 sociotechnical orientations, 2 psychosocial orientations and 13 presented psychosociotechnical orientations. With only a few exceptions, several issues related to nursing unit layouts were investigated no more than one time in any one category of research orientations. Several other seemingly important issues including patient and family behavior and perception, health outcomes and social and psychosocial factors in relation to unit layouts have not been studied adequately. Research limitations/implications: – Future studies on nursing unit layouts will need to focus on patient and family behavior and perception, health outcomes and social and psychosocial factors in different units. They will also need to focus on developing theories concerning the effects of layouts on the technical, psychological and social dimensions of nursing units. Originality/value: – Despite a long history of research on nursing unit layouts, an integrative review of these studies is still missing in the literature. This review fills in the gap using a novel framework for integrative review developed based on research orientations.